Novel radiation sources using relativistic electrons - Applications - Karabarbounis, A.; Trikalinos, Ch.; Papadakis, I.; Sarros, S. (HNPS Advances in Nuclear Physics, 2020)
Novel sources of radiation using relativistic electrons in periodic structures are being briefly discussed based on different mechanisms and producing radiation of very different characteristic. In this article we will focus among others on the Smith-Purcell effect and the many efforts made since their discovery 55 years ago. Especially Smith-Purcell (SP) free- electron lasers (FELs) using low energy electron beam are being seen as attractive option for a compact source of coherent terahertz radiation. The latter refers to the production of radiation in the THz gap region associated with many applications including very promi- sing and interesting results on imaging techniques in Medicine as well as applications in Biology, Molecular Physics etc. We will present calculations of Radiation Factors based on the Smith-Purcell radiation production with very interesting characteristics and discuss the possibility of calculating and designing a complete system of coherent THz radiation production based on a Smith-Purcell FEL.